The Effect of Using VOA Podcast on Students Intensive Listening Skill - Gulo, Andre Gemuruh; Ikhsanudin; Rahmani, Eka Fajar (Universitas Cokroaminoto Palopo, 2023)
The purpose of this research was to find out the effect of podcast or VOA podcast in improving the eight grade students English listening skill. This research utilized a sample of 30 students from a class, comprising 13 males and 17 females. Data collection for this research involved the use of measurement techniques, specifically the gap-filling test as the instrument. The collected data was analyzed to assess the impact of podcasts on students' listening skills. The results of the study revealed a significant improvement in students' listening skills with a t-value of 7.131, exceeding the critical value of 2.045 (t-value = 7.131, df=29). This indicated a significant impact of using podcasts in EFL students' listening learning (7.131 > 2.045) with a medium effect size of 0.77. Therefore, the findings suggest that the use of podcasts effectively contributed to the improvement of students' listening skills.